Long-term effects of simulated gastric juice alternated with brushing on hardness, substance loss, flexural strength and reliability of CAD-CAM monolithic materials (Journal of Applied Oral Science, 2022)
Objectives: The purpose of this study is to evaluate, over a simulated 5-year period, the effect of simulated gastric juice alternated with brushing on CAD-CAM monolithic materials considering microhardness, substance loss, flexural strength, and reliability of the materials. Methodology: Blocks from Lava Ultimate (LU), Vita Enamic (VE), IPS Empress CAD (EMP), IPS e.max CAD (EMAX), and Vita Suprinity (VS) were milled into cylinders and sliced into disks. The EMAX and VS were crystallized, and all specimens were polished with silicon carbide papers and allocated as follows: 1) artificial saliva + brushing or 2) simulated gastric juice (0.113% hydrochloric acid (HCl) solution in deionized water, pH 1.2) + brushing, simulating 1, 3, and 5 years of clinical function. Each year of clinical function was simulated by three repetitions of immersion for 3 hours in artificial saliva or simulated gastric juice followed by 1,217 brushing cycles. The microhardness and substance loss were evaluated at baseline (T0) and at each year by using a Vickers hardness tester and an analytical balance. The biaxial flexural strength (BFS) test was performed in a mechanical testing machine at the end of the 5th year. Weibull modulus was calculated from the BFS data. Results: The microhardness of the LU was not influenced by the treatment, whereas that of the other materials, in certain years, was significantly lower in the gastric juice + brushing groups in comparison with artificial saliva + brushing groups. In general, the materials did not present a significant change in microhardness over time, for either of the treatments. The LU alone showed greater substance loss in the gastric juice + brushing groups for every year. In both treatments, the LU, VE, and EMP exhibited a significant increase in the substance loss over time. The treatment did not affect the BFS of the materials. The gastric juice + brushing decreased the reliability of the VE. Conclusions: All materials were somehow impaired by the gastric juice + brushing in at least one of the evaluated parameters, except for the BFS. However, in a deeper analysis, the LU would be the least indicated materials, followed by VE, for patients with eating disorders.